2022
DOI: 10.1155/2022/7905120
|View full text |Cite
|
Sign up to set email alerts
|

Selected Spatiotemporal and Joint Angle Parameters in Normal Gait and Nordic Walking with Classical and Mechatronic Poles in Aspects of Sex Differences

Abstract: Introduction. The aim of this study was to compare selected spatiotemporal parameters and changes in the range of motion in the joints of lower and upper limbs during normal gait and during Nordic walking performed with classical and mechatronic poles of females and males. Methods. The study involved 19 physical education students (11 males and 8 females). The MyoMotion research motion analysis system was used to collect gait kinematic variables. The subject task was to cover a 100 m distance in a straight lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Secondly, we asked all participants to wear comfortable clothing and shoes during the testing session to minimise any additional effects on their gait pattern. Finally, we acknowledge that previous studies [30,31] and our own studies [32,33] have shown that the presence of IMU sensors does not interfere with natural movement nor alter gait patterns, and any differences in joint angle measurement can be attributed to the variability in the anatomical models used for calculations. The MyoMOTION MR3 sensors used in our study are small, lightweight, and wireless and are attached directly to the body and poles.…”
Section: Limitations Of the Conducted Studymentioning
confidence: 80%
“…Secondly, we asked all participants to wear comfortable clothing and shoes during the testing session to minimise any additional effects on their gait pattern. Finally, we acknowledge that previous studies [30,31] and our own studies [32,33] have shown that the presence of IMU sensors does not interfere with natural movement nor alter gait patterns, and any differences in joint angle measurement can be attributed to the variability in the anatomical models used for calculations. The MyoMOTION MR3 sensors used in our study are small, lightweight, and wireless and are attached directly to the body and poles.…”
Section: Limitations Of the Conducted Studymentioning
confidence: 80%
“…Probably, the warm-up and cool down exercises of the adapted NW also played an important role in determining the observed results, as they can stimulate the myofascial meridians with degrees of movement very similar to those reached during the adapted ME, probably closing the flexibility gap between the disciplines. In fact, in women, the average ranges of motion for the shoulders, hips, knees, and ankles during NW practice are approximately a mean value of 13 • (flexion-extension), 54 • (flexion-extension), 72 • (flexion-extension), and 54 • (dorsi-plantarflexion), respectively [44], whereas in adapted ME practice, the amplitude of the movements increases gradually until it reaches the physiological limits of the mentioned joints (but not only) through multi-joint movements involving the lines listed in Table 1. However, both adapted NW and ME included movements stimulating sensory refinement, slow-motion stretch, and elastic recoil in a fascial-oriented direction [45].…”
Section: Discussionmentioning
confidence: 99%
“…1). IMU sensors enabled data recording and comprehensive analysis with a sampling frequency of 200Hz 22 . The subject's task was to cover a 100-meter distance with three types of walking -walking without sticks, walking with classic NW sticks, and walking with mechatronic sticks.…”
Section: Testing Methodsmentioning
confidence: 99%